Implementation of Bridge Management System on Interurban Bridge in Maluku Province - Erwin Marasabessy (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2015)
Bridges as transport infrastructures play a vital role in smoothing traffic flows. The success of a bridge in playing its role and serving its function depends on its management. The Directorate General of Highways of the Ministry of Public Work has used a system to manage bridges known as the Bridge Management System (BMS). The system allows a systematic plan and provides a uniform procedure for all bridge operation activities on the national and provincial level. Data from Implementation Agency of National Inter-Urban Roads of Area IX, Northern Maluku in 2011 indicates that the total length of national roads in Maluku Province is 15,238.01 M, with a total of 562 bridges. In Ambon Island, especially, there are 52 bridges totaling 1,176.25 m in length. The study was conducted at several inter-urban bridges in Maluku Province of Ambon Island: Wai Batu Merah, Wai Ruhu, Wai Lawa, Wai Yari and Wai Tua bridges. Assessment of bridge structure conditions was conducted visually to determine the conditions of the existing bridges comprehensively by referring to the Bridge Management System (BMS) complemented with a computer-based Bridge Management Information System (BMIS). Condition scores for the five bridges—Wai Batu Merah, Wai Ruhu, Wai Lawa, Wai Yari, and Wai Tua, according to Bridge Management System, are 2, 1, 2, 1, and 2 respectively. The scores of the five bridges indicate that their physical condition can be categorized as good or with minor defects. Based on technical screening, the proposed treatment for Wai Batu Merah, Wai Ruhu, Wai Lawa, dan Wai Tua bridges is the rehabilitation of their sub-elements. As for the Wai Yari Bridge, the treatment will be maintained regularly. The defect repair costs are IDR 149,138,238.00, IDR 81,048,000.00, IDR 174,579,106.10, IDR 79,233,324.01 and IDR 238,323,258.60 for Wai Batu, Wai Ruhu, Wai Lawa, Wai Yari, and Wai Tua Bridges, respectively.